Transcriptomics and Metabolomics Identify Drug Resistance of Dormant Cell in Colorectal Cancer - Xie, Lang; Huang, Renli; Huang, Hongyun; Liu, Xiaoxia; Yu, Jinlong (Frontiers in Pharmacology, 2022)
Background: Tumor dormancy is an important way to develop drug resistance. This study aimed to identify the characteristics of colorectal cancer (CRC) cell dormancy. Methods: Based on the CRC cohorts, a total of 1,044 CRC patients were included in this study, and divided into a dormant subgroup and proliferous subgroup. Non-negative matrix factorization (NMF) was used to distinguish the dormant subgroup of CRC via transcriptome data of cancer tissues. Gene Set Enrichment Analysis (GSEA) was used to explore the characteristics of dormant CRC. The characteristics were verified in the cell model, which was used to predict key factors driving CRC dormancy. Potential treatments for CRC dormancy were also examined. Results: . The dormant subgroup had a poor prognosis and was more likely to relapse. GSEA analysis showed 2 defining characteristics of the dormant subgroup, a difference in energy metabolism and synergistic effects of cancer-associated fibroblasts (CAFs), which were verified in a dormant cell model. Transcriptome and clinical data identified LMOD1, MAB21L2, and ASPN as important factors associated with cell dormancy and verified that erlotinib, and CB-839 were potential treatment options. Conclusions: Dormant CRC is associated with high glutamine metabolism and synergizes with CAFs in 5-FU resistance, and the key effectors are LMOD1, MAB21L2, and ASPN. Austocystin D, erlotinib, and CB-839 may be useful for dormant CRC.